Comparison between Graphene and GaAs Quantized Hall Devices with a Dual Probe - Payagala, Shamith U. (IEEE Trans Instrum Meas, 2020)
A graphene quantized Hall resistance (QHR) device fabricated at the National Institute of Standards and Technology (NIST) was measured alongside a GaAs QHR device fabricated by the National Research Council of Canada (NRC) by comparing them to a 1 kΩ standard resistor using a cryogenic current comparator. The two devices were mounted in a custom developed dual probe that was then assessed for its viability as a suitable apparatus for precision measurements. The charge carrier density of the graphene device exhibited controllable tunability when annealed after Cr(CO)(3) functionalization. These initial measurement results suggest that making resistance comparisons is possible with a single probe wired for two types of quantum standards – GaAs, the established material, and graphene, the newer material that may promote the development of more user-friendly equipment.